The influence of self-control on gaze behaviour and performance under pressure - Englert, C.; Oudejans, R. R. D.; Bertrams, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Under pressure athletes are not always capable of controlling their attention leading to possible performance impairments (e.g., Oudejans & Pijpers, 2010). According to the strength model of self-control attention regulating is a self-control act that is energized by a limited metaphorical strength. This resource can deplete after a primary act of self-control and is not immediately replenished which can negatively impact subsequent self-control (e.g., Baumeister, Gailliot, DeWall, & Oaten, 2006). In a series of studies by Englert and Bertrams (2012) the anxiety-performance relationship was moderated by self-control, as athletes with sufficient self-control strength were able to counteract the negative anxiety effects on attention and performance. In the current study we wanted to expand these findings by applying eye tracking technology to analyze attention regulation under pressure. Methods: In a mixed between (depletion: yes vs. no)- within (anxiety: yes vs. no) design (N = 28), we assumed that self-control strength moderates the relationship between anxiety and dart performance. Furthermore we tested whether self-control negatively affects attention with an eye tracking device. Participants were randomly assigned to a depletion or non-depletion condition and we manipulated self-control strength (e.g., Englert & Bertrams, 2012). We manipulated anxiety by asking participants to perform a series of dart throws low and high (order counterbalanced) on a climbing wall (e.g., Nibbeling et al., 2012). Results: In the anxiety condition depleted participants performed significantly worse than participants from the non-depletion condition while there were no group differences low on the climbing wall. Depleted participants high on the climbing wall displayed a significantly shorter quiet eye period compared to participants from the non-depletion condition. There were no group differences in gaze behavior low on the climbing wall. Discussion: Developing interventions to foster self-control strength could enable athletes to perform at a high level under pressure (e.g., Baumeister et al., 2006).